(untitled) (Research, Society and Development, 2021)
Objective: This study promotes an evidence-based reflection on the forms of obstetric violence available in the Brazilian literature. Methods: This is an integrative literature review carried out using the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF) and Medical databases. Literature Analysis and Retrieval System Online (MEDLINE). From the initial search with defined descriptors and Boolean operator, 52 studies were found in the selected databases and after applying the inclusion and exclusion criteria, 12 studies were selected to compose the review. Results and Discussion: The places covered in the studies were public and mixed (private) hospitals affiliated to the SUS. Obstetric violence, a term recognized by the World Health Organization (WHO), is based on the appropriation of women’s autonomy and reproductive processes by health professionals, in the form of dehumanized treatment, abusive medication or abusive interference with natural processes. The various types of physical, verbal and psychological violence were highlighted, as well as the performance of unnecessary procedures, highlighting the high rate of cesarean sections occurring out of context and exposing the woman to three times the risk of death by childbirth. Conclusion: And it was possible to observe the great difference in the dissemination of what obstetric violence is and how it is imperative to reinforce the rights of women, which ensure humanized care, as well as studies on its approach to prenatal care.